2018
DOI: 10.1055/s-0043-104665
|View full text |Cite
|
Sign up to set email alerts
|

Patientenkontrollierte Analgesie: Methoden, Handhabung und Ausbaufähigkeit

Abstract: Patient-controlled analgesia (PCA) is one of the well established methods for the treatment of postoperative pain. A cochrane-review concluded that PCA is associated with better postoperative pain ratings and improved patient-satifaction compared to traditional way of administering opioids. Some prerequisites concerning patient selection, education of the patient and the medical staff, and supervision during PCA therapy are mandatory for a safe use of PCA. Current PCA modalities (intravenous and epidural route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 34 publications
0
3
0
2
Order By: Relevance
“…Because opioids are likely to be administered more than necessary due to basal infusion of IV-PCA, they can occasionally cause serious adverse events. 18 Effective regional analgesia is important to discontinue IV-PCA, so we adopted regional procedures such as preincisional infiltration, intraoperative intercostal nerve block, and surgeon-guided continuous serratus anterior plane block. In previous studies, preemptive local anesthesia was related to a significant reduction in postoperative wound pain after VATS, 15 and single-injection intercostal nerve block was associated with a reduction in postoperative pain and clinically noninferior to thoracic epidural analgesia or paravertebral block.…”
Section: Discussionmentioning
confidence: 99%
“…Because opioids are likely to be administered more than necessary due to basal infusion of IV-PCA, they can occasionally cause serious adverse events. 18 Effective regional analgesia is important to discontinue IV-PCA, so we adopted regional procedures such as preincisional infiltration, intraoperative intercostal nerve block, and surgeon-guided continuous serratus anterior plane block. In previous studies, preemptive local anesthesia was related to a significant reduction in postoperative wound pain after VATS, 15 and single-injection intercostal nerve block was associated with a reduction in postoperative pain and clinically noninferior to thoracic epidural analgesia or paravertebral block.…”
Section: Discussionmentioning
confidence: 99%
“…PCA is one of the accepted methods for the management of postoperative pain. A cochrane review concluded that PCA was associated with better postoperative pain scores and increased patient satisfaction compared with traditional modes of analgesic drug administration (Abrolat et al, 2018). Intravenous PCA has been widely used for postoperative analgesia over the past few decades (Hadi et al, 2006;Kim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…[61] Postoperative pain is usually controlled by patient-controlled analgesia. [62] The use of noninvasive transdermal analgesics (such as lidocaine, fentanyl, and morphine) overcomes the problems associated with patient-controlled analgesia. For example, iontophoresis can drive fentanyl molecules through the skin into the systemic circulation.…”
Section: Iontophoresismentioning
confidence: 99%